Re-Eksistensi Tap MPR: Potret dalam Pembahasan dan Orbit Materi Muatan - Rido, Ali; Nugraha, Riko; M. Imam Nasef (As-Siyasi: Journal of Constitutional Law, 2022)
The re-existence of the TAP MPR has sparked academic interest, but there are still aspects that have gone unnoticed, namely those related to the study of the legislative struggle and why the TAP MPR is included in the types and hierarchy of laws and regulations. The re-existence of the TAP MPR ultimately has legal implications, so it is important to initiate the direction of its content material in the future. Therefore, this paper examines these issues with the aim of enriching the academic space for discussion regarding the re-existence of the TAP MPR. This study was carried out in a juridical-normative manner using a statutory approach and using secondary legal sources in the form of primary legal materials of the 1945 Constitution of the Republic of Indonesia, Law No. 12 of 2011 and UU No. 13 of 2022, minutes on the formation of laws and decisions of the Constitutional Court, and secondary legal materials, which include text books and law journals. This study found that the re-existence of the TAP MPR, apart from being a guideline for establishing a state in Indonesia, is also a direction so that the formation of laws and regulations does not deviate from the basis of the state. As for the future TAP MPR content model, this can be realized through beschickking and regelling. The two models of content material must be guided by strict requirements so that their formation is in line with the principle of conformity between types, hierarchies, and content material of laws and regulations. So it can be concluded that there are still various MPR TAPs that are relevant to be used as guidelines in the state, so it is important to emphasize them in the cluster of laws and regulations. Aside from being a foundation for the state to be in line with the law, it is also a direction so that the formation of the PUU under it does not deviate from the basic direction of the state.